A Benchmark of Density Functional Approximations For Thermochemistry and Kinetics of Hydride Reductions of Cyclohexanones. Issue 6 (26th June 2019) - Deraet, Xavier; Woller, Tatiana; Van Lommel, Ruben; De Proft, Frank; Verniest, Guido; Alonso, Mercedes
Abstract: The performance of density functionals and wavefunction methods for describing the thermodynamics and kinetics of hydride reductions of 2‐substituted cyclohexanones has been evaluated for the first time. A variety of exchange correlation functionals ranging from generalized gradient approximations to double hybrids have been tested and their performance to describe the facial selectivity of hydride reductions of cyclohexanones has been carefully assessed relative to the CCSD(T) method. Among the tested methods, an approach in which single‐point energy calculations using the double hybrid B2PLYP−D3 functional on ωB97X−D optimized geometries provides the most accurate transition state energies for these kinetically‐controlled reactions. Moreover, the role of torsional strain, temperature, solvation, noncovalent interactions on the stereoselectivity of these reductions was elucidated. Our results indicate a prominent role of the substituent on the cis / trans ratios driven by the delicate interplay between torsional strain and dispersion interactions. Abstract : A recipe for hydride selectivity : A combined computational and experimental approach was undertaken to impose order onto the chaotic tangle of predictive models for hydride stereoselectivity. Based on an extensive benchmark study, we present a two‐fold computational recipe able to perfectly reproduce and interpret our experimental data for the reduction of 2‐substituted cyclohexanones with LiAlH4 .